REPRESENTASI TOKOH PEREMPUAN FEMINIS DALAM NOVEL ANNE OF GREEN GABLES KARYA L.M. MONTGOMERY - Maghfira Najwa Azahra (Cahaya Ilmu Bangsa Institute, 2025)
This research aims to analyse how feminist representation is shown by the main character in the novel Anne of Green Gables by L.M. Montgomery. The research method used is descriptive qualitative with library research technique. The research data are dialogues and monologues in the novel identified as feminist representations. This research refers to Simone de Beauvoir's concept of Existentialist Feminism. The results show that the discrimination experienced by the main character is gender-based discrimination related to criticism of her appearance. In the aspect of education, Anne faces social barriers that limit women from accessing higher education and pursuing careers. The efforts made by the main character to free herself from all forms of discrimination received are by showing independence and strong determination in achieving her goals. Through the efforts made by the main character to fight discriminatory attitudes, Anne represents a woman who dares to oppose discrimination and fight for gender equality.Penelitian ini bertujuan untuk mengungkap bagaimana representasi feminis ditunjukkan oleh tokoh utama dalam novel Anne of Green Gables karya L.M. Montgomery. Metode yang digunakan adalah deskriptif kualitatif dengan teknik studi kepustakaan (library research). Data penelitian berupa dialog dan monolog dalam novel yang teridentifikasi sebagai representasi feminis. Penelitian ini mengacu pada konsep Feminisme Eksistensialis Simone de Beauvoir. Hasil penelitian menunjukkan bahwa diskriminasi yang dialami oleh tokoh utama yaitu diskriminasi berbasis gender terkait kritik atas penampilannya. Pada aspek pendidikan, Anne menghadapi hambatan sosial yang membatasi perempuan untuk mengakses pendidikan tinggi dan mengejar karier. Upaya yang dilakukan oleh tokoh utama untuk membebaskan diri dari segala bentuk diskriminasi yang diterima adalah dengan menunjukkan kemandirian dan tekad kuat dalam mencapai tujuannya. Melalui upaya yang dilakukan tokoh utama untuk melawan sikap diskriminatif, Anne merepresentasikan sosok perempuan yang berani menentang diskriminasi dan memperjuangkan kesetaraan gender.